The Crucial Role of Charge Accumulation and Spin Polarization in Activating Carbon‐Based Catalysts for Electrocatalytic Nitrogen Reduction. (3rd February 2020) - Yang, Yuanyuan; Zhang, Lifu; Hu, Zhenpeng; Zheng, Yao; Tang, Cheng; Chen, Ping; Wang, Ruguang; Qiu, Kangwen; Mao, Jing; Ling, Tao; Qiao, Shi‐Zhang
Abstract: Cost‐effective carbon‐based catalysts are promising for catalyzing the electrochemical N2 reduction reaction (NRR). However, the activity origin of carbon‐based catalysts towards NRR remains unclear, and regularities and rules for the rational design of carbon‐based NRR electrocatalysts are still lacking. Based on a combination of theoretical calculations and experimental observations, chalcogen/oxygen group element (O, S, Se, Te) doped carbon materials were systematically evaluated as potential NRR catalysts. Heteroatom‐doping‐induced charge accumulation facilitates N2 adsorption on carbon atoms and spin polarization boosts the potential‐determining step of the first protonation to form *NNH. Te‐doped and Se‐doped C catalysts exhibited high intrinsic NRR activity that is superior to most metal‐based catalysts. Establishing the correlation between the electronic structure and NRR performance for carbon‐based materials paves the pathway for their NRR application. Abstract : 1 und 1 zusammengezählt : Rechnerische und experimentelle Studien wurden kombiniert, um den katalytischen Charakter von Materialien auf Kohlenstoffbasis für die elektrokatalytische Stickstoffreduktionsreaktion (NRR) systematisch zu ermitteln. Te‐ und Se‐dotierte C‐Katalysatoren zeigen die höchste intrinsische NRR‐Aktivität.